A Christmas Carol (2019)
Students of the Language Programme at Universidad de Antioquia, El Carmen De Viboral. This work is intended as a pedagogical tool and it is the product of one of the activities carried out during the semester 2018-02 in the English Literature Course, taught by Martha Pulido.